Evaluation of the Performance of Natural Fiber Reinforced Polymer Composites - Surahman Ramli, Muhammad; Kalam, Anizah; Md. Yusof, Fauziah; Yuni, Ibrahim (International Journal of Engineering and Technology, 2018)
Natural fibers provide an alternative to artificial fiber as composite reinforcement, which can transform the industrial trend into more eco-friendly. Hence an investigation of the mechanical properties of banana and kenaf fibers reinforced polymer composites were conducted.Â Two composite systems were prepared by using alkali treated Banana fibers at several Sodium Hydroxide concentrations (0%, 3%, 6% and 9%) and hybrid Banana fibers (BF) and kenaf fibers at various ratio of BF/Kenaf fibers (0/100, 30/70, 50/50, 70/30, 100/0).Â The composites were fabricated using banana fiber and hybrid BF/kenaf fiber to reinforce epoxy and unsaturated polyester composite respectively using hand layup method.Â The tensile and flexural tests were then performed on the composites specimen according to ASTM D3036 and ASTM D790 respectively.Â The result indicates that treated banana fibers have a significant effect on the Flexural strength and Tensile Modulus.Â Meanwhile, hybridisation has achieved the highest tensile strength of 0/100 composite composition while the lowest was by 100/0 which is 20.04 MPa and 10.33 MPa respectively. The tensile strength gradually decreases as the concentration of kenaf reduced. In comparison with the flexural test, it shows the same trend as the tensile test where flexural strength directly proportional to the concentration of kenaf fiber.Â The highest tensile modulus was achieved by 0/100 at 3.24 GPa while the lowest was achieved by 100/0. This was expected as the strength of kenaf was better compared to the banana fiber. For the hybrid composite, 30/70 had the highest toughness compare to the other specimen. In conclusion, the tensile and flexural strength directly influences by the percentage of kenaf fiber. The higher the percentage of kenaf fiber, the higher the tensile and flexural properties. Hybridization improves the specimen in term of strain and toughness. This indicates that the hybrid composite was able to absorb higher energy before failure.Â Â